Le Terrorisme : Un Concept Abusé, Une Menace Réelle. Le Cas De La République Démocratique Du Congo - François Sadiki Koko; Fraternel Amuri Misako (European Scientific Journal, ESJ, 2017)
The Democratic Republic of the Congo (DRC), an important role player within the international community, has not escaped the widespread trend relating to the abuse of the terrorist concept. Whether it is about the rebels of the Movement of 23 March (M23) or the combatants of the Allied Democratic Forces / National Army for the Liberation of Uganda (ADF/NALU), the Congolese government has made use of the terrorist concept to describe these peace spoilers in eastern DRC. Furthermore, the government spokesperson qualified the civic movements known as Lucha and Filimbi as terrorist organizations. Yet, such extreme positions taken by government did not prevent the latter from entering into direct peace talks with the M23 leadership in Kampala (Uganda). Nor did it discourage the President from personally meeting with a delegation of Lucha and Filimbi in Goma. This article analyses the contradictions surrounding the phenomenon of terrorism: an abused concept describing a real contemporary societal threat. It subsequently applies this concept to the DRC's case. The central argument of the article is that the exploitation of the terrorist concept by Congolese political and media actors is likely to contribute towards impeding a full understanding of a phenomenon that, otherwise, represents a real security threat to the fragile Congolese state. In so doing, this exploitation prevents the formulation of relevant strategies designed to eradicate this phenomenon. In terms of methodology, observation and documentary investigation involving the content analysis were mobilized for this study.